How Miners and Other Professional Groups Perceive the Benefits and Risks of Hard Coal Mining: A Study on the Role of the Affect Heuristic - Zielonka, Piotr; Białaszek, Wojciech; Dzik, Bartłomiej; Wybrańczyk, Katarzyna (Frontiers in Psychology, 2021)
The problems inherent in the transformation of the energy sector are visible in countries where the hard coal mining industry plays an important role. For the transition to be successful, the social perception of the mining industry should be taken into account. This study empirically examines the role of affect in the perception of the economic benefits, occupational dangers and environmental threats of the hard coal mining industry. The affect heuristic may seriously distort the perception of risks associated with coal mining by those who have skin in the game. We show that benefitting from hard coal mining reduces the perceived risk associated with hard coal. Since the economic and social benefits of hard coal elicit positive affect in miners, it diminishes their concerns about occupational safety and the detrimental environmental impact of the mining industry. The affect heuristic may be responsible for the failures of many information campaigns.